Protection of civilians from sexual violence in armed conflict in Africa - (:unkn) unknown (My University, 2016)
Unfortunately sexual violence had a history of omission in international law until the end of the twentieth century. There were very few explicit provisions in international humanitarian law and international human rights law. This legal hiatus has been partially filled by the work of the international criminal court.
Keywords: African Research